Modelo matemático de un sistema coordinado productor-comprador bajo el enfoque VMI - Torres, Fidel; Ballesteros, Frank; Villa, Marcela (Ingeniería, 2012)
This work develops a new coordinated manufacturer-buyer model for a single item in a vendor-managed inventory (VMI) context. The proposed model includes the manufacturing uptime and a manufacturer-buyer synchronization scheme. This mechanism makes logistical coordination between manufacturer and buyer much easier. The analysis of the mathematical model of coordination considers production and demand rates, as well as totals of the manufacturer and the buyer’s ordering and holding inventory costs. This study is complemented by a sensitivity analysis. It focuses on the effects of parameter variations on proposed performance measurements in the manufacturer-buyer VMI coordinated scheme. Finally, analytical conditions under which the suggested coordinated implementation of VMI gives benefits to both manufacturer and buyer and to the supply chain are deduced and verified.